2021
DOI: 10.1177/00131245211048440
|View full text |Cite
|
Sign up to set email alerts
|

Five Important Parental Involvement Variables that Affect Young Children’s Mathematical Achievements: A Comparative Study

Abstract: Success in mathematics has been shown to increase career opportunities; thus, improving student learning in mathematics is vital for educational policymakers. This study investigated the effects of five parental involvement variables on young children’s mathematical achievements in 10 countries, including seven Arab countries, and found significant effects for all of them. Students who attended pre-primary education achieved higher mathematics scores compared to those who did not. Students who had been helped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
3
0
5
Order By: Relevance
“…This finding is in line with several previous studies which state that parental involvement is very important for students and has been proven to have an effect on their academic performance (Jang et al, 2021;Krishnan & A, 2019). Students who get good help and attention from their parents have been shown to get higher achievements (Alreshidi et al, 2021). Parental involvement is one of the external motivational factors that can promote student academic achievement (Womack & Johnson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with several previous studies which state that parental involvement is very important for students and has been proven to have an effect on their academic performance (Jang et al, 2021;Krishnan & A, 2019). Students who get good help and attention from their parents have been shown to get higher achievements (Alreshidi et al, 2021). Parental involvement is one of the external motivational factors that can promote student academic achievement (Womack & Johnson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the parental factors that relate to variability within the math homework-helping environment. A study conducted in seven Arab countries revealed that children with parents who are more frequently involved in their math homework have lower math achievement [29]. The researchers suggest that parents may exhibit controlling behaviors that may interfere with children's learning.…”
Section: Parent Math Anxiety and Math Achievement In The Context Of M...mentioning
confidence: 99%
“…As proposed by Alreshidi and colleagues [29], parents who are frequently involved in their children's math homework may be more intrusive in the process. In line with this, previous research has identified parents' lower math achievement and higher math anxiety as factors that are associated with fewer autonomy-supportive and more controllingsupportive homework-helping behaviors [32].…”
Section: Parent Math Anxiety and Math Achievement In The Context Of M...mentioning
confidence: 99%
“…Las expectativas educativas se estudian de manera recurrente debido a su correlación con el nivel académico alcanzado, la deserción y la desigualdad experimentada por el estudiante (Ali et al, 2022;Almroth et al, 2020;Alreshidi et al, 2022;Lorenz et al, 2020;Salazar et al, 2020;Van Den Berghe et al, 2022) Las expectativas educativas de los estudiantes son una percepción propia de la posibilidad de alcanzar un determinado nivel de formación escolar como estudiante (Madeeha et al, 2022).…”
Section: Expectativas Educativas De Los Estudiantes Y Rendimiento Aca...unclassified
“…La presente investigación tuvo como objetivo identificar una brecha, interpretada como desigualdad, entre las expectativas educativas y el rendimiento académico entre diferentes antecedentes migratorios (Alreshidi et al, 2022;Lopez-Agudo et al, 2021;Madeeha et al, 2022;Palacios-Abad, 2021) Asimismo, se identificaron factores estadísticamente significativos que influyen en las variables independientes mencionadas en un contexto argentino (OECD, 2019b).…”
Section: Introductionunclassified